Route chauffante et étude de dédoublement de la RN 01 sur 04 Km : du PK 254 + 000 au PK 258 + 000 - Titi, Ahmed; Bederina, Madani, Directeur de thèse (My University, 2018)
There are now different ways to harness the direct energy of the Sun using photovoltaic solar panels transforming light and infrared energy into electrical energy or thermal sensors allowing the direct use of thermal energy of the Sun, or to transform it into mechanical and then electrical energy. Our end-of-study project is composed of two parts, in the first part we have done a bibliographic synthesis of the research works realized in the field of the heating road and its applications in several countries and we proposed this technique on a section 500m road. In the second part we studied in detail the splitting of the RN23 over 4 km from PK 254 + 000 to PK 258 + 00
Laghouat : Université Amar Telidji - Département de génie civil Option : Voies et ouvrages d'art